Peran Language Immersion Dalam Pembelajaran Bahasa Arab - Nurul Hikmah (Lugawiyyat, 2023)
Language Immersion (LI) Is a useful program for second language learning, Second language is a medium for learning all subject matter and some activities in the classroom and also outside the classroom, The language is immersed by students anytime and under any circumstances by listening, speaking, reading, writing, and culture as well. Language Immersion in this study focused on Arabic. Language Immersion In learning Arabic is very important to foster a sense of love for students towards Arabic, Language Immersion Is where a student can prioritize Arabic habituation before understanding the rules of Arabic, Students first know early about language behavior before knowing the grammar to be learned afterwards, Students who do this Language immersion will be able to become good pronunciations of the language as well as This research is a descriptive research analysis where researchers collect all scientific material from original sources then read it and translate it, classify it and compile it into their own writing. What is the importance of the immersion linguistics program in learning Arabic for non-native speakers and 2.What is the Language immersion program. The result of this study is that the Language immersion program is very important in teaching foreign languages and this program has a great position among other foreign language learning programs. This program has the privilege of teaching languages quickly and fluently.